Decoration of glassy carbon surfaces with dendrimer-encapsulated nanoparticles with a view to constructing bifunctional nanostructures - Ju, Heeyoung; Koo, Chong Min; Kim, Joohoon (ROYAL SOC CHEMISTRY, 2011)
We demonstrate a method for constructing bifunctional nanostructures, which conjugate biochemical and electrocatalytic activities, on glassy carbon surfaces by decorating the carbon surfaces with both biologically active glucose oxidases and size-monodisperse Pt nanoparticles (less than 2 nm in diameter) utilizing only a single dendrimer layer.
Keywords: COVALENT MODIFICATION; ELECTROCHEMICAL OXIDATION; OXYGEN REDUCTION; DIAZONIUM SALTS; ELECTRODES; CATALYSIS; PLATINUM; FILMS; SIZE; PD